Implicit Instruction, Subtitles, Vocabulary and Listening Comprehension - Eny Kusumawati; Hasan Hasan (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2018)
This current study is focusing on the impact of English movies with English subtitles and Bahasa Indonesia subtitles on content comprehension of English movies through the students’ listening comprehension. Fifty-six (56) students of English subject at the Politeknik Elektronika Negeri Surabaya were selected randomly. Using the quasi-experimental study, a movie entitled Transcendence was selected based on the ESP content and language level difficulty.  With two intact groups, they were group A and group B presented the same movie, class A watched it with English subtitle and class B with Bahasa Indonesia subtitle. After watching the movie, the participants answered the relevant multiple-choice vocabulary by listening session questions and content comprehension questions, they answer the questions on the paper. The data gathered were subjected to the statistical procedure of paired sample t-test. The results showed that English subtitle has an impact better than Bahasa Indonesia subtitle. However, this statistical data failed to show that they get greater development on their vocabulary comprehension. Those findings showed that the students’ listening comprehension does not have any impact on their vocabulary comprehension.